The language effect in international trade: A meta-analysis - Peter Egger; Andrea Lassmann (Center for Economic Studies and ifo Institute (CESifo), 2011)
Gravity models of international trade have been frequently applied to estimate the impact of common (official or spoken) language on bilateral trade. This study provides a meta-analysis based on 701 language effects collected from 81 academic articles. On average, a common (official or spoken) language increases trade flows directly by 44%.
Keywords: C21; O40; H54; R11; 330; common language; gravity; international trade; trade costs; Internationale Wirtschaftsbeziehungen; Mehrsprachigkeit; Gravitationsmodell; Meta-Analyse; Welt